Plasmid DNA-loaded asymmetrically porous membrane for guided bone regeneration. (10th February 2021) - Oh, Se Heang; Byun, June-Ho; Chun, So Young; Jang, Young-Joo; Lee, Jin Ho
Abstract: Although bone defects can be restored spontaneously, bone reconstruction with sufficient strength and volume continues to be a challenge in clinical practices. In recent years, the use of a variety of biomaterials with bioactivity has been attempted to compensate for this limitation. Herein, we fabricated a pDNA (encoding for BMP-2)-loaded asymmetrically porous polycaprolactone (PCL)/Pluronic F127 membrane as a bioactive guided bone regeneration (GBR) membrane, using a modified immersion-precipitation method. It was observed that the GBR membrane allows continuous release of pDNA for more than 20 weeks. The pDNA was sufficiently transfected into human bone marrow stem cells ( h BMSCs) without significant cytotoxicity and the gene-transfected cells showed prolonged synthesis of BMP-2. From in vitro osteogenic differentiation and in vivo animal studies, the effective induction of osteogenic differentiation of h BMSCs and enhanced bone regeneration by the pDNA-loaded asymmetrically porous PCL/Pluronic F127 membrane was observed, suggesting that the pDNA-loaded membrane as a bioactive GBR membrane can be an alternative therapeutic technique for effective bone regeneration.